Ethics in the Qurʾān and the Tafsīr Tradition : From the Polynoia of Scripture to the Homonoia of Exegesis - Moqbel, Tareq Hesham, (Middle East and Islamic Studies E-Books Online, Collection 2024., 2024)
This book is about the articulation of ethics in the QurÊ¾Än and the tafsÄ«r tradition. Based on an examination of several apparently problematic QurÊ¾Änic narrative pericopes and how the exegetes grappled with them, the book demonstrates that the moral world of the QurÊ¾Än is polyvalent and non-linear, owing, above all, to its intrinsic ethical antinomies and textual ambiguities. That is, the book contends that paradox and uncertainty are both constituents of the QurÊ¾Än's ethical architectonics, and that through these constituents the QurÊ¾Än charts a system of ethics that seeks to tread in the midst of a non-ideal world rife with uncertainty. The book also argues that the tafsÄ«r tradition tends to erode the hermeneutical openness of the QurÊ¾Än and, thereby, limits the QurÊ¾Än's ethical potential. The book, thus, advances our understanding of QurÊ¾Änic ethics and contributes to the field of tafsÄ«r studies and to the scholarship on QurÊ¾Änic hermeneutics.